Digital disruption and Karawitan recordings: Paradigm shifts, aesthetic challenges, and opportunities for cultural preservation - Santoso, Iwan Budi; Pujiono, Bagong; Darno, Darno (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
This article explores how digital recording practices, amid contemporary technological transformation, rearticulate the musical meaning of karawitan, reshape listening experience, and reorganize its modes of cultural circulation. The study is situated within broader scholarly debates on digital mediation, particularly concerning the shifting relationship between recorded sound and the socio-spatial and ritual contexts that have historically constituted karawitan performance. Using a descriptive qualitative case-study approach, the research draws on in depth interviews with musicians (pengrawit), scholars, distributors, and listeners, supported by observations of recording environments, patterns of online circulation, archival sources, and indicators of platform based distribution. The findings indicate that the disembedding of sound from live performance settings constrains the transmission of inter-musician interaction, spatial resonance, and ritual presence, while technical standardization in digital production tends to narrow improvisational scope and dynamic responsiveness. Concurrently, the increasing dominance of internet platforms such as YouTube and Spotify substantially broadens access and accelerates global circulation, yet also fosters listening practices oriented toward immediacy and fragmentation. Rather than portraying digitalization as a unidirectional process of cultural loss, this study reveals a structural tension between expanded reach and altered experiential depth, underscoring the need for context-aware recording strategies and digital curation models capable of supporting the sustainable transmission of karawitan in the digital era.